Molecular identification of Theileria equi, Babesia caballi, and Rickettsia in adult ticks from North of Xinjiang, China. Issue 6 (26th August 2021) - Zhang, Yang; Wen, Xiuxiu; Xiao, Peipei; Fan, Xinli; Li, Min; Chahan, Bayin
Abstract : Background: Ticks in Xinjiang distribute widely and account for one third of China. Ticks can carry and transmit bacteria, virus, and parasite. However, the research of tick‐borne pathogens in Xinjiang is rather little. Objective: To understand the situation of hard tick carry Theileria equi, Babesia caballi and Rickettsia spp. of Zhaosu and Altay in Xinjiang. Methods: In this study, 119 tick samples were obtained from horses in Xinjiang, China, Ticks were identified morphologically to determine species and PCR was used to investigate the situation of pathogens by hard ticks. Results: One hundred and seven belong to Dermacentor marginatus, five belong to D. niveus, and seven belong to D. silvarum. Theileria equi and Babesia caballi were detected in one tick and 18 ticks, respectively. However, the carrying rate of Rickettsia spp. was 51.26% (61/119). Among these, the mixed carriage rate of T. equi and Rickettsia spp. was 0.8% (1/119). The mixed carriage rate of B. caballi and Rickettsia spp. was 10.1% (12/119). Conclusion: Our results revealed that hard tick can carry not only haeimoparasite but also many important zoonotic pathogens in Xinjiang, and this situation was worth heeding. Abstract : One hundred nineteen tick samples obtained from horses in Xinjiang, China, to investigate the situation of pathogens by hard ticks. Theileria equi was detected in 1 tick, Babesia caballi was detected in 18 ticks. Among this, the mixed carriage rate of Theileria equi and Rickettsia was 0.8% (1/119), the mixed carriage rate of Babesia caballi and Rickettsia was 10.1% (12/119).